2022
DOI: 10.1002/cpp.2728
|View full text |Cite
|
Sign up to set email alerts
|

New directions in the mental health care of migrants, including refugees—A randomized controlled trial investigating the efficacy of value‐based counselling

Abstract: Objective: Specialized literature has identified a need for evidence-based, lowthreshold, short-term, and intracultural psychological interventions that can be made available to migrants, including refugees, who suffer from psychological symptoms in host countries. The objective of the present study is to measure the efficacy of valuebased counselling (VBC) as such an intervention.Method: We conducted a pragmatic, rater-blinded randomized controlled trial employing a pre-post control group design to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Looking at the studies with large effect size estimates (SMD ≥ .80) in adult samples, six studies emerged (Ali, 2020;De Graaff et al, 2020;Koch et al, 2020;Orang et al, 2022;Renner et al, 2011;Shaw et al, 2021). In a study with moderate risk of bias, De Graaff et al ( 2020 (2020) found constantly larger effect sizes for the same program in a population of adult Syrian refugees in the Netherlands, Spaaij ( 2022) -yet in a feasibility and acceptability trial -reported nonsignificant but inverse effect sizes for a sample of Syrian refugees and asylum seekers in Switzerland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the studies with large effect size estimates (SMD ≥ .80) in adult samples, six studies emerged (Ali, 2020;De Graaff et al, 2020;Koch et al, 2020;Orang et al, 2022;Renner et al, 2011;Shaw et al, 2021). In a study with moderate risk of bias, De Graaff et al ( 2020 (2020) found constantly larger effect sizes for the same program in a population of adult Syrian refugees in the Netherlands, Spaaij ( 2022) -yet in a feasibility and acceptability trial -reported nonsignificant but inverse effect sizes for a sample of Syrian refugees and asylum seekers in Switzerland.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the remaining four studies with large effect sizes in adult samples was associated with at least 'some concerns' for risk of bias in three out of five domains (Ali, 2020;Orang et al, 2022;Renner et al, 2011;Shaw et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, according to a number of refugee studies, attention is being paid to the positive resources of refugees ( 63 ). As a result of conducting value-based counseling on refugees, enhancing the client's self-efficacy and ultimately demonstrating their inherent resilience, it was found that most psychological indicators, such as depression and anxiety, improved in comparison to the control group ( 64 ). Therefore, it is crucial to create a strength-based therapeutic environment that helps NKDs receive direct support when necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The present paper presents the data collected on variables of resilience and perspective taking. Two recent papers which focused on further data collected for the study focused on the clinically meaningful reduction of depression and PTSD symptoms, perceived stress, anxiety, and somatic complaints experienced by participants in the VBC group after an average of four counselling sessions [43,44].…”
Section: Trial Designmentioning
confidence: 99%
“…When large numbers of refugees began to arrive in Germany in 2015, the approach was used to empower migrants and refugees resettled in Germany, as it corresponds well with the specific needs of mobile, culturally heterogeneous populations like migrants and refugees. Two recent studies investigating the effectiveness of VBC in this context revealed significant symptom reductions with medium to large effect sizes [43,44].…”
Section: Introductionmentioning
confidence: 99%